Public Relations Services of the Ministry of Religious Affairs of South Sumatra Province in Providing Public Information Based on WhatsApp Artificial Intelligence Chatbot - Febiola Dinda Natalia; Heri Junaidi; Badaruddin Azarkasyi (International Journal of Health, Economics, and Social Sciences (IJHESS), 2026)
Public Relations of the Ministry of Religious Affairs of South Sumatra Province faces challenges in providing public information services due to the high volume of public inquiries through digital channels, while human resource capacity is limited, so the previous response time reaches 5-8 hours. As an innovation, AIOHumas, which is an Artificial Intelligence (AI) chatbot based on WhatsApp, was developed. This study aims to analyze public information services through AIOHumas and its improvement strategies. The research uses a descriptive qualitative approach based on the New Public Service Theory (Denhardt & Denhardt, 2003). Data was collected through semi-structured in-depth interviews and documentation studies of three key informants, namely the Head of the Public Relations Working Team, the Website Manager and AIOHumas, and the AIOHumas PIC. Data analysis used the Miles and Huberman interactive model. The results of the study show that AIOHumas meets five indicators of modern public services, namely responsiveness (response in seconds and operating 24 hours), transparency (official data is validated), accountability (periodic data updates every three months by a dedicated data team), accessibility (reaching around 6,000 users through familiar platforms), and participation (unanswered questions are used as database development materials). Service improvement is realized through strengthening the 24-hour automated system, expanding service coverage, continuous data updates, and humanizing digital services in AIOHumas version 3 which sets standards for polite, friendly, and empathetic communication. This innovation won the 1st place award "Work Unit with Innovative Communication" level Regional Office in 2025, although it still faces the constraint of dependence on internet infrastructure and centralized management of one to two people.